(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of basic technical skills of passing over, passing under, smashing, and serving at the Netral Sidole Junior club. This research method uses a quantitative descriptive method. The sample in this study was all volleyball players of the Netral Sidole Junior Club, which is known to have a total of 18 players. While the data collection technique used a test instrument. The results of this study based on the results of descriptive analysis of research data from passing over, passing under, smashing, and serving showed that the category for female athletes of the Netral Sidole Junior Club, for the Very Good category as much as 0%, the Good category as much as 30%, the Enough category as much as 50%, the Less category as much as 10%, and the Very Less category 10%. For the category of male athletes of the Netral Sidole Junior Club, the Very Good category as much as 0%, the Good category as much as 25%, the Enough category as much as 63%, the Less category as much as 0%, and the Very Less category has 13%. This study concludes that the basic technical skills possessed by athletes of the Netral Sidole Junior club are in the Enough category. The researcher’s suggestion is to increase the portion of training, improve the training program, because that is a provision for improving performance.